Warm-up strategies of professional soccer players: practitioners' perspectives - Towlson, C.; Midgley, A. W.; Lovell, R. (Journal of Sports Sciences, 2013)
Recent research has challenged the typical pre-match and half-time (HT) interval warm-up (WU) routines currently used by professional soccer players. This study surveyed 2010/11 season WU strategies and their underpinning scientific reasoning and situational factors via an internet-based questionnaire, which was distributed to English Premier League and Championship practitioners, of which 43% responded. The pre-match WU duration was 30.8 (8.2) min, ranging between 15-45 min, and 89% of practitioners administered a WU of = 25 min. Respondents also reported a 12.4 (3.8) min period between the end of the WU and match kick-off. Eighty-nine per cent recognised the physiological benefits of re-WUs during this "down-time" period, with 63% instructing players to engage in such activity. During HT, 58% instructed players to re-WU either on the pitch or within stadia facilities, but "unwillingness of the coach/manager" (42%) and a "lack of time" (63%) were major constraints. Practitioners reported that 2.6 (1.6) min might be available for HT re-WUs. Factors such as match regulations, league policy, and stadia facilities were not generally considered as major barriers to the delivery of WUand re-WU strategies. We suggest that researchers consider the time-demands and barriers faced by practitioners whendeveloping experimental designs to examine WU regimens.